Suckling behavior of calves in seasonally calving pasture-based dairy systems, and possible environmental and management factors affecting suckling behaviors. - Cuttance EL; Mason WA; McDermott J; Laven RA (Elsevier Inc and the Federation of Animal Science Societies (FASS) Inc on behalf of the American Dairy Science Association, 2022)
In recent years, interest has been increasing in whether farmed animals are able to live a reasonably natural life, with one particular area of concern being calf-dam separation. The objectives of this study were to monitor the timing and frequency of suckling behavior of calves left on pasture to suckle their dams for up to 24 h (interquartile range 4.0-15.5 h) and to investigate possible risk factors that may contribute to any variability seen. Over 2 yr, a convenience sample of 8 farms (4 in the North Island, 4 in the South Island of New Zealand) were involved in an observational study where cows and calves were observed for 24 h a day over a 2-wk-long period per farm. During the observation period, farmers continued to remove calves at the same frequency they normally did (which ranged from once a day to 4 times a day). Cows (between 2 and 12 yr old) and calves were observed from a scissor lift in or beside the calving paddock. Cows had numbers written on them, and observers used binoculars and spotlights. Observers recorded the length of stage 2 labor, time of birth, standing, and first suckling, number of suckling events, time of calf removal from the dam, temperature where the cows were grazing, and size of the grazing area they were calving in. Dams were body condition scored before calving, and their age was extracted from farm records. A total of 697 calves were observed during the study. A total of 444 of 697 calves [63.7%; 95% confidence interval (CI) = 60.0-67.3%] suckled in the calving paddock (farm range 40.0% to 90.2%). Of the 444 calves that suckled in the calving paddock, 407 (58.4%; 95% CI 54.6-62.1%) suckled within the first 6 h after birth (farm range 33.0% to 83.6%). Individual risk factors associated with the hazard rate ratio (HR) for time to first suckling event were time to standing (calves who took more than 1.3 h to stand had a longer time from birth to first suckle) and age of the dam [compared with calves that were born from dams >7 years of age, calves born to dams that were 2-3 and 4-7 yr of age had a 1.49 (95% CI 1.07-2.06) and 1.19 (95% CI 0.89-1.60) HR, respectively, for time from birth to first suckle in the calving paddock]. Farm risk factors associated with the HR of suckling were frequency of calf collection [calves that were born on farms that collected calves once a day suckled earlier than calves on farms that removed calves more than once a day (HR 1.52; 95% CI 1.25-1.84)] and temperature [a minimum temperature of <10°C within 6 h of a calf being born was associated with a 0.69 (95% CI 0.53-0.89) hazard of suckling in the calving paddock]. We observed very large farm variability that urgently requires further investigation if pasture-based farms are ever to adopt a system where calves remain with their dams for longer than 24 h.
Keywords: dairy calves; dams; pasture; risk factors; suckling; Animals; Cattle; Farms; Female; New Zealand; Parturition; Pregnancy; Proportional Hazards Models; Risk Factors